Study of Method of Evaluating Surface's Pollution Level & Cleaning Efficiency on Decoration Building Materials (International Journal of Architecture and Urbanism, 2024)
In the paper, we analyzed synthetically the research results on methods of testing the cleaning effect on DBM(Decoration Building Materials) and suggested a new Pollution Level & Cleaning Effect Evaluation System(PCEES) on the DBM's surface which is based on image information processing by use of color quantization method and color feature extraction method with HSI (Hue Saturation Intensity) model.By applying the PCEES to many building objects, we could select the effective composition of cleaning agent and cleaning method and calculate the agent's consumption amount necessary for the building work.And we suggested the degree of cleaning effect according to the quantitative result values of evaluation on pollution level & cleaning effect to correspond with the empirical judgment of a man.